Proposed new interior design scheme of Islamic Islamic Treatment Centre at Jalan 8/35, Seksyen 8 43650 Bandar Baru Bangi, Selangor for Darussyifa' / Muhaini Kornan - Kornan, Muhaini (Faculty of Architecture, Planning and Surveying, 2010)
Interior Design is a way to solving problems and designers have to figure out the issues that linked to those problems. The designer’s have to came out with best functional design. In order to achieve the best design, designer should understand on all information. Interior design is not something easy. Many criteria should be taken into consideration during process they carried out. The understanding on spatial arrangement, concept and design theme should align with will and client needs. As time went by, the design should be something that could fulfill public people needs. Concentrate in fulfilling the people need, all the information that has been studied must be used in the design process.